POWER FOR GROWTH: G20 ECONOMIC POLICY AND INVESTMENTS - Filipović, Miroslava; Mihajlović, Milan Đ; Karović, Samed (Poslovna ekonomija, 2019)
The Group of Twenty (G20) has taken a premier role in devising a multistructural set of rules and recommendations for a new global economic regime. The paper identifies the G20 agenda development, detects major principles and norms for the issue area of investment, and concludes with an examination of some of the G20 results. The paper concludes that the G20 regime may prove effective if the commitments are upheld, more international actors involved, and a more balanced approach taken in devising such a regime.